1994
DOI: 10.1002/j.1460-2075.1994.tb06509.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational alterations in transmembrane topology of the hepatitis B virus large envelope protein.

Abstract: The preS domain at the N‐terminus of the large envelope protein (LHBs) of the hepatitis B virus is involved in (i) envelopment of viral nucleocapsids and (ii) binding to the host cell. While the first function suggests a cytosolic location of the preS domain during virion assembly, the function as an attachment site requires its translocation across the lipid bilayer and final exposure on the virion surface. We compared the transmembrane topology of newly synthesized LHBs in the endoplasmic reticulum (ER) memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
179
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(192 citation statements)
references
References 28 publications
11
179
0
2
Order By: Relevance
“…However, it has been described earlier that point mutations in this pre-S region have an important function in HBV morphogenesis by inhibiting virion formation. 36,37 These data were confirmed by our studies that showed that the secreted viral particles were dramatically reduced. Additionally, electronmicroscopy studies revealed that the extracellular appearance of viral and subviral particles was impaired, showing a screw-like pattern of filaments and a fried-egg-like shape of virions.…”
Section: Discussionsupporting
confidence: 65%
“…However, it has been described earlier that point mutations in this pre-S region have an important function in HBV morphogenesis by inhibiting virion formation. 36,37 These data were confirmed by our studies that showed that the secreted viral particles were dramatically reduced. Additionally, electronmicroscopy studies revealed that the extracellular appearance of viral and subviral particles was impaired, showing a screw-like pattern of filaments and a fried-egg-like shape of virions.…”
Section: Discussionsupporting
confidence: 65%
“…Surprisingly, little density is observed in the three-dimensional maps of the compact and gapped particles in the 20 Å-wide-gap between nucleocapsid and envelope (Figure 2; Supplementary Figure 4). However, this gap should not only contain the 120 resolved spikes of the nucleocapsid (aa 63-94), but also the 47 amino acids per cytosolic loop I (33-79, according to assignment in UniProt Q60GL2HBV) and another five amino acids per cytosolic loop II (200-204, according to assignment UniProt Q60GL2HBV) plus the Nterminal domains of the L-HBs with inverted topology (probably one in 12 HBs molecules, given an L:M:S ratio of 1:1:4 and 50% of L-protein molecules bearing preS inside; Heermann et al, 1984;Bruss et al, 1994). This adds up to a total of about 32 000 residues (ca.…”
Section: Organization Of Hbs In the Envelopementioning
confidence: 99%
“…PreS1 of the L-protein plays a crucial role in envelopment of the capsid (Bruss, 1997) and specific receptor interaction with hepatocytes (Glebe and Urban, 2007). In order to fulfill this dual role, L-adopts two alternate topologies with PreS (PreS1 þ PreS2) either located at the inside or the outside of the viral membrane (Bruss et al, 1994). Remarkably, structural analysis of the HBV preS1-domain revealed that it is intrinsically unfolded (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…5 The L protein can adopt two different transmembrane topologies, allowing the exposure of the N-terminal preS domain at either the luminal or the cytosolic side of the ER membrane. 6 This latter form is essential during HBV morphogenesis to establish a protein-protein interaction between the cytoplasmic core particle and a specific sequence within the preS domain of the L protein. 7,8 One peculiarity of HBV morphogenesis compared with that of other viruses is that the surface proteins not only envelop the nucleocapsid to form a mature virion, they are capable of forming subviral empty spherical or filamentous particles in the absence of nucleocapsid.…”
mentioning
confidence: 99%